Video Content of Menek Daha Ceremony (Ngeraja Sewala and Ngeraja Singha) as Audio Visual Learning Media - I Wayan Sudiarta; Dewa Gede Hendra Divayana; I Gde Wawan Sudatha (Universitas Pendidikan Ganesha, 2024)
Currently, with the development of technology, situational images related to insight and knowledge regarding commonly carried out religious ritual practices can be disseminated via digital platforms. This article aims to analyze the suitability of videos broadcast on YouTube with the content of the Ngeraja Sewala and Ngeraja Singha ceremonies in the Balinese Hindu community tradition as effective audio-visual learning media. This study uses a qualitative descriptive method by collecting data from videos on the YouTube platform conducting content analysis and evaluating the criteria for effective audio-visual learning media. Content analysis was carried out on the videos that had been collected. Continued with the process of processing data that has been collected and analyzed, through a qualitative approach and presenting it in the form of descriptions. The results of the study found that video content containing information about the Menek Daha ceremony (Ngeraja Sewala and Ngeraja Singha) which had been published via the YouTube platform was grouped into three types, namely: 1) Ordinary video documentation that is not intended as a medium for conveying more complete information to its viewers, 2) Documentary videos that include informative narrations where the sound narration and scenes in the video are out of sync, and 3) Video tutorials that make the source narrate direct and dominant in the video where between the narration and picture scenes are shown in sync.